Tingkah laku vandalisme dalam kalangan pelajar sekolah menengah kebangsaan di Zon Labis, Johor - Gan, Swee Eng (2013)
This research was done to look into the factors influencing vandalism among the students in Johor. This research was done in the Labis Zon,Segamat Johor. The research subjects consist of 100 students from among Form 1 and Form 2 students. Questionnaires used included subject’s personal details, types of vandalism, family, school, peer factor and also self-concept. Data analysis used the Statistical Package for the Social Science 12.0 (SPSS-12.0). From the result gained it showed that different parents’ income and education level have effects on vandalism occurred among the students. Besides, the result of the research also showed that family background, school background, peer background, and self-concept influenced the vandalism occurred among the school students. The result from this research may be used for reference in the future.